THE ARMENIAN MASSACRES IN ALEXANDRAPOL DISTRICT FROM MAY TO NOVEMBER 1918: A LITTLE-STUDIED EPISODE FROM THE HISTORY OF THE ARMENIAN GENOCIDE - Hayrapetyan, Armen (Armenian Folia Anglistika, 2025)
The article deals with the study of the demographic policy pursued by the Turkish authorities in the occupied Alexandrapol district. On the basis of newly discovered archival documents, scientific literature, memoirs of eyewitnesses and reports of periodicals it is shown that in the period from May to November 1918 Turkish regular troops with the support of local Muslims pursued a policy of genocide of Eastern Armenians, distorting the ethnic image of the population of the district.The data obtained also show that the official statistics of the Turkish crimes in Alexandropоl district does not reflect the true scale of what happened and is significantly underestimated.
Keywords: Alexandropol district; demographic policy; Turkish crimes; Genocide; Khoyetsyan; Shirak; Pambak